Analisis Pengaruh Stuktur Modal, Ukuran Perusahaan dan Profitabilitas terhadap Price Earning Ratio (PER) Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2015 - Yosi Yosi Stefhani (Jurnal Manajemen, 2018)
The purpose of this study is to determine whether there is influence of capital structure (Debt To Equity Ratio), firm size (total assets) and profitability (Net Profit Margin) to Price Earning Ratio (PER) at manufacturing companies listed in Indonesia Stock Exchange period 2013-2015 . The sample of companies in this study there are 30 manufacturing companies listed on the IDX period 2013-2015. Data analysis technique used is multiple regression. The independent variables in this research are DER, Total Asset and NPM. Dependent variable in this research is PER. The results showed that only NPM affected PER while Total Asset and NPM did not affect PER. The results also show simultaneously all independent variables affect LQ 45.